(untitled) (Andamios, Revista de Investigación Social, 2025)
This article examines the phenomenon of youth homicide in Mexico City using a mixed-methods approach that critically engages with the theoretical frameworks of juvenicide and the sociology of crime. Through a variable-oriented analysis, it investigates factors such as levels of marginalization, educational attainment, the presence of organized crime, alcohol sales, and the availability of firearms. The results reveal a significant association between these factors and the risk of youth homicide, underscoring the need for more comprehensive analysis. This research contributes to the accumulation of empirical evidence and highlights the relevance of juvenicide as a category for understanding the violent deaths of young people.